2014
DOI: 10.1186/1749-8090-9-33
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of temporary epicardial pacing wires use after valve surgery

Abstract: BackgroundAlthough temporary cardiac pacing is infrequently needed, temporary epicardial pacing wires are routinely inserted after valve surgery. As they are associated with infrequent, but life threatening complications, and the decreased need for postoperative pacing in a group of low risk patients; this study aims to identify the predictors of temporary cardiac pacing after valve surgery.MethodsA retrospective analysis of data collected prospectively on 400 consecutive valve surgery patients between May 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
18
1
Order By: Relevance
“…Although need of EPW can be questioned in selected cases, i.e. low-risk aortic valve replacement [6–8], presence of these wires can be very helpful in weaning from cardiopulmonary bypass or improving cardiac output in the early postoperative period [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Although need of EPW can be questioned in selected cases, i.e. low-risk aortic valve replacement [6–8], presence of these wires can be very helpful in weaning from cardiopulmonary bypass or improving cardiac output in the early postoperative period [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified age, 10‐13 preoperative arrhythmia, 10,11,13 diabetes, 13 higher NYHA class, 12 high pulmonary pressures, 12 certain medications, 11,12 certain types of valve surgery, 11,12 heavy annular calcification, 12 longer cross‐clamp time, 12 and pacing on separation of CPB 10,13 as predictors of TEPW need. While there are some variability in findings, in general older, more comorbid patients are more likely to require pacing following cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They also found selective placement of TEPW was safe, with 42% of patients not receiving TEPW. They had no negative consequences with this selective placement strategy 12 . In our study, we examined isolated patients with AVR which has not been done previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple means by which wires may be affixed to the right atrium including direct suture or clipping, or through the use of an atrial button. Previous investigators have demonstrated that numerous patient factors may be associated with the subsequent need for temporary pacing such as advanced age, NYHA III-IV, pulmonary hypertension, digoxin use, multiple valvular replacement, long cross-clamp time and annular calcification [ 4 ]. In the majority of cases, pacer wires are not used and in fact, some surgical groups have recommended more selective insertion, particularly with low-risk surgery such as elective off-pump coronary bypass grafting [ 5 ].…”
Section: Discussionmentioning
confidence: 99%